2017
DOI: 10.1002/jssc.201701014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of molecularly‐imprinted polymers for extraction of sanshool acid amide compounds followed by their separation from pepper oil resin derived from Chinese prickly ash (Zanthoxylum bungeanum)

Abstract: Molecularly imprinted polymers were prepared using the molecular structure analogs of sanshool as template molecule, 2-vinylpyridine and β-cyclodextrin as double functional monomers, ethylene dimethacrylate as cross linker, and azobisisobutyronitrile as initiator. The structural characteristics of the polymers were determined by Fourier-transform infrared spectroscopy and scanning electron microscopy. Dynamic adsorption and isothermal adsorption were also investigated. The molecularly imprinted polymers were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Chen et al. [ 21 ] reported a SPEC based on a MIP with methylacryloyl‐β‐CD and 2‐VP as bi‐functional monomers to separate acid amide components from pepper oil resin derived from Chinese prickly ash. The MIP exhibited selective capability of the target components with a saturated concentration of 45.04 μg mg −1 .…”
Section: Molecularly Imprinted Polymers With Cyclodextrin As Functional Monomersmentioning
confidence: 99%
“…Chen et al. [ 21 ] reported a SPEC based on a MIP with methylacryloyl‐β‐CD and 2‐VP as bi‐functional monomers to separate acid amide components from pepper oil resin derived from Chinese prickly ash. The MIP exhibited selective capability of the target components with a saturated concentration of 45.04 μg mg −1 .…”
Section: Molecularly Imprinted Polymers With Cyclodextrin As Functional Monomersmentioning
confidence: 99%
“…Then, when 60:40 v/v ratio of methanol/water was used, the IF of MIP 3 was >20 in comparison to MIP 5 having an IF of 1.117 which indicated that MIP 3 had a better binding behavior. These results were expected due to the basic nature of 4-VP, which enhanced its binding to acidic templates [7]. Also, it was found from previous studies that 4-VP could be successfully used as a functional monomer for other phenolic acids as chicoric acid [10], caffeic acid [18], cinnamic acid, and ferulic acid [25,26].…”
Section: Functional Monomers Molar Ratiosmentioning
confidence: 65%
“…They are able to bind selectively to their target molecule while it is present among structural analogues of similar size and structure. MIPs have numerous advantages, which made them of high interest to researchers nowadays . They have widely been used in purification, separation, and are promising candidates for drug delivery applications .…”
Section: Introductionmentioning
confidence: 99%
“…Among these metabolites, aliphatic amides, which are classified as sanshools, are the major active components. They have a unique pungent taste and cause paresthetic sensations on the tongue 5 . Furthermore, sanshools and their analogues have been shown to induce apoptosis of human hepatocarcinoma HepG2 cells and block expression of the oncogene KCNK9 6,7 .…”
Section: Introductionmentioning
confidence: 99%